1990
DOI: 10.1037/0033-2909.107.1.82
|View full text |Cite
|
Sign up to set email alerts
|

The illusion of reality: A review and integration of psychological research on hallucinations.

Abstract: Hallucinations are among the most severe and puzzling forms of psychopathology. Although usually regarded as first-rank symptoms of schizophrenia, they are found in a wide range of medical and psychiatric conditions. Moreover, a substantial minority of otherwise normal individuals report hallucinatory experiences. The purpose of this article is to review the considerable research into the cognitive mechanisms underlying (particularly psychotic) hallucinations that has been carried out and to integrate this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
370
1
20

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(417 citation statements)
references
References 166 publications
24
370
1
20
Order By: Relevance
“…Such an impaired reality testing might foster misattribution of internally generated experiences, which in turn may promote hallucinatory reports (e.g. Bentall, 1990;Cahill & Frith, 1996). Indirect evidence for the idea of a specific response bias comes from studies finding a considerable overlap between fantasy proneness, schizophrenia-like phenomena, and dissociation (Merckelbach, Muris, Horselenberg, & Stougie, 2000;Merckelbach, Rassin, & Muris, 2000;Watson, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an impaired reality testing might foster misattribution of internally generated experiences, which in turn may promote hallucinatory reports (e.g. Bentall, 1990;Cahill & Frith, 1996). Indirect evidence for the idea of a specific response bias comes from studies finding a considerable overlap between fantasy proneness, schizophrenia-like phenomena, and dissociation (Merckelbach, Muris, Horselenberg, & Stougie, 2000;Merckelbach, Rassin, & Muris, 2000;Watson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have suggested that hallucinations exist on a continuum ranging from relatively benign forms to pathological manifestations as seen in schizophrenia (see review by Bentall, 1990). Indeed, several studies have indicated that a non-trivial minority of the normal population reports having had hallucinatory experiences at some point in their lives (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizotypy refers to psychometrically-measured behavioral traits and dispositions associated with schizophrenia, but present in the non-clinical population [27][28] . The validity of schizotypy has been supported by factor analytical studies that have linked schizotypal traits to schizophrenic symptoms 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, LDHS participants have been argued to be more responsive to dreams and regressions and positive hallucinations profiles, which may require greater utilization of fantasy and imagery and depend upon strong episodic retrieval strategies (Barber, 1999;Hilgard, 1964). Alternatively, if the HDHS subtype is characterized by a monitoring deficit during hypnosis (Kunzendorf & Boisvert, 1996), they may be more responsive to hallucination suggestions because of impaired monitoring of the source of perceptual representations and the concomitant misattribution of the content to the environment (Bentall, 1990; see also Brown & Oakley, 2004). Finally, if HDHS participants possess a greater propensity for automatizing behavior and compartmentalizing information (Barber, 1999), they would be expected to exhibit greater responsiveness to the posthypnotic compulsions profile, which may depend on the execution of implementation intentions outside of awareness.…”
Section: Introductionmentioning
confidence: 99%